Pengarusutamaan Berita Desa Oleh Gerakan Desa Membangun (GDM) Sebagai Upaya Kontrahegemonik - Tristia riskawati; Dede Mulkan (Jurnal Kajian Jurnalisme, 2017)
This research aims to understand the mainstreaming of village news by Gerakan Desa Membangun (Building Village Movement). The method used is collective case study using an approach of critical paradigm. Desa Melung, Kabupaten Banyumas and Desa Cibiru Wetan, Kabupaten Bandung are observed. The research shows that mainstreaming of village news by Building Village Movement is an endeavour of contra-hegemony because it attempts to create an alternative media as a rival to mainstream media. The mainstreaming of village news by Building Village Movement is significant in encouraging villagers to share informations as well as attracting academics attention to its movement.